Doppler Echocardiography in Infancy and Childhood - Hofbeck, Michael; Deeg, Karl-Heinz; Rupprecht, Thomas (Springer International Publishing : Imprint: Springer, 2017)
This book covers the full range of Doppler echocardiography in infants and children, documenting the wide variety of potential findings with the aid of a wealth of high-quality images. The imaging features of more than 20 conditions on conventional two-dimensional echocardiography, pulsed wave, continuous wave and color Doppler imaging are described and depicted, drawing attention to differential diagnostic criteria and other issues of importance in everyday clinical practice. Each condition is individually addressed, covering all relevant aspects, and helpful information is also provided on the normal examination. The book is supplemented by more than 500 videos demonstrating typical findings of two-dimensional and color Doppler echocardiography. Special chapters focus on the differential diagnosis of cyanotic infants and echocardiography specifically for the neonatologist. The authors' aim in compiling this book is to equip the reader with the knowledge required in order to employ Doppler echocardiography optimally and to interpret findings confidently and correctly. Doppler Echocardiography in Infancy and Childhood will be an invaluable reference for echocardiographers, pediatricians, neonatologists, and pediatric and general radiologists.
Keywords: Medicine.; Radiology.; Pediatrics.; elektronické knihy; electronic books